Fetal Tracheal Occlusion Increases Lung Basal Cells via Increased Yap Signaling - Serapiglia, Vincent; Stephens, Chad A.; Joshi, Rashika; Aydin, Emrah; Oria, Marc; Marotta, Mario; Peiro, Jose L.; Varisco, Brian M. (Frontiers in Pediatrics, 2022)
Fetal endoscopic tracheal occlusion (FETO) is an emerging surgical therapy for congenital diaphragmatic hernia (CDH). Ovine and rabbit data suggested altered lung epithelial cell populations after tracheal occlusion (TO) with transcriptomic signatures implicating basal cells. To test this hypothesis, we deconvolved mRNA sequencing (mRNA-seq) data and used quantitative image analysis in fetal rabbit lung TO, which had increased basal cells and reduced ciliated cells after TO. In a fetal mouse TO model, flow cytometry showed increased basal cells, and immunohistochemistry demonstrated basal cell extension to subpleural airways. Nuclear Yap, a known regulator of basal cell fate, was increased in TO lung, and Yap ablation on the lung epithelium abrogated TO-mediated basal cell expansion. mRNA-seq of TO lung showed increased activity of downstream Yap genes. Human lung specimens with congenital and fetal tracheal occlusion had clusters of subpleural basal cells that were not present in the control. TO increases lung epithelial cell nuclear Yap, leading to basal cell expansion.